1997
DOI: 10.1080/01688639708403870
|View full text |Cite
|
Sign up to set email alerts
|

A review of mild head trauma. part I: Meta-analytic review of neuropsychological studies

Abstract: We conducted a meta-analytic review of neuropsychological studies of mild head trauma (MHT). Studies were included if they met these criteria: patients studied at least 3 months after MHT; patients selected because of a history of MHT rather than because they were symptomatic; and attrition rate of less than 50% for longitudinal studies. Studies of children were not considered. We found a total of 8 published papers with 11 samples that met these criteria. Using the g statistics, the overall effect size of 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
269
3
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 464 publications
(295 citation statements)
references
References 24 publications
21
269
3
2
Order By: Relevance
“…Belanger et al (2005) perPersistent post-concussive syndromeformed a meta-analysis of 39 studies involving 1463 cases of mTBI assessing clinical neuropsychological test findings. Their findings were similar to what has also been described by Binder et al (1997), Frencham et al (2005), and Schretlen & Shapiro (2003), implicating short-term, but not necessarily long-term neuropsychological effects, except for those cases who were in litigation, where either "stable or worsening of cognitive functioning over time (p. 215) was observed." Mooney et al (2005), in a university based rehabilitation service, examined those with "disappointing recoveries" and observed that "in cases of poor recovery after mTBI where compensation or litigation may be a factor, most of the variance in recovery seems to be explained by depression, pain, and symptom invalidity (p. 975) ."…”
Section: Limitations Of Neuropsychological Research To Advance the Fisupporting
confidence: 83%
“…Belanger et al (2005) perPersistent post-concussive syndromeformed a meta-analysis of 39 studies involving 1463 cases of mTBI assessing clinical neuropsychological test findings. Their findings were similar to what has also been described by Binder et al (1997), Frencham et al (2005), and Schretlen & Shapiro (2003), implicating short-term, but not necessarily long-term neuropsychological effects, except for those cases who were in litigation, where either "stable or worsening of cognitive functioning over time (p. 215) was observed." Mooney et al (2005), in a university based rehabilitation service, examined those with "disappointing recoveries" and observed that "in cases of poor recovery after mTBI where compensation or litigation may be a factor, most of the variance in recovery seems to be explained by depression, pain, and symptom invalidity (p. 975) ."…”
Section: Limitations Of Neuropsychological Research To Advance the Fisupporting
confidence: 83%
“…Evidence clearly suggests that, for most people, the cognitive effects of mTBI resolve within days to three months post-injury (for meta-analyses see: Belanger et al, 2005;Frenchman et al, 2005;Schretlen & Shapiro, 2003). Yet, despite generally good long-term prognosis for individuals who experience a mTBI, a subset report the subjective experience of chronic cognitive deficits, especially in attention and memory (e.g., Dikmen, Machamer, Fann, & Temkin, 2010;Hartlage, Durant-Wilson, & Patch, 2001;Binder, Rohling, & Larrabee, 1997;Rimel, Giordani, Barth, Boll, & Jane, 1981).…”
Section: Prognosis and Recoverymentioning
confidence: 99%
“…Although deficits have been found in speed of information processing, memory, attention and executive functions, both the clinical significance and the etiology of these deficits have been questioned (Binder, 1997;Binder et al, 1997).…”
Section: Introductionmentioning
confidence: 99%